FENOLOGI PEMBUNGAAN PADA TANAMAN WIJAYA KUSUMA (Ephiphylum oxypetalum) - Yovita Harmiatun (Jurnal Pro-Life, 2016)
Research of flowering phenology has been conducted on Wijaya Kusuma (Ephiphylum oxypetalum). The study was conducted in September 2012 - February 2013. This research aims to determine the effect of light and wind to the flowering phenology in E. oxypetalum. Total of 20 pots of Wijaya Kusuma placed at two different locations. Total of 10 pots of Wijaya Kusuma placed at quite light with lot of wind, and 10 pots placed in the shade with little wind. Wijaya Kusuma were placed in the shade vegetative growth faster than the others. Wijaya Kusuma were placed in quite light with lot of wind begun flowering at 8-16 weeks after planting. Flowering begun with the appearance of prospective interest in phylocladia node. Candidates flowers will bloom on the ninth day and bloom only 1-2 hours at midnight. Flowers wither on the tenth day and fall on day thirteen. Wijaya Kusuma were placed in the shade and a little wind is not flowering, but flowering may be induced by placing its in a bright place and a lot of wind. In this study concluded that wind and light affect the process of flower formation in plants Wijaya Kusuma. Keywords: Ephiphylum oxypetalum, Phenology, Flowering